Whole exome sequencing revealed a novel homozygous variant in the DGKE catalytic domain: a case report of familial hemolytic uremic syndrome - Soraya Gholizad-kolveiri; Nakysa Hooman; Rasoul Alizadeh; Rozita Hoseini; Hasan Otukesh; Saeed Talebi; Mansoureh Akouchekian (BMC, 2020)
Abstract Background Atypical hemolytic uremic syndrome (aHUS) is a rare disease characterized by microangiopathic hemolytic anemia caused by small vessel thrombosis, thrombocytopenia, and renal failure. The common cause of aHUS is a dysregulation in the alternative complement pathway. Mutations in none complement genes such as diacylglycerol kinase epsilon (DGKE) can also result in this syndrome. Case presentation Here, we report on a 19-year-old female with the clinical diagnosis of aHUS, who has unaffected consanguineous parents and an older sibling who was deceased from aHUS when she was seven months old. We performed whole exome sequencing (WES) followed by evaluation of detected variants for functional significance, using several online prediction tools. Next, in order to confirm the detected pathogenic variant in proband and segregation analysis in her family, Sanger sequencing was done. The novel variant was analyzed in terms of its impact on the protein 3-dimensional structure by computational structural modeling. The results revealed that the proband carried a novel homozygous missense variant in DGKE located in exon 6 of the gene (NM_003647.3, c.942C > G [p.Asn314Lys]), and in silico analysis anticipated it as damaging. Protein computational study confirmed the influence of potential pathogenic variant on structural stability and protein function. Conclusion We suggest that some variations in the catalytic domain of DGKE like p.Asn314Lys which can cause alterations in secondary and 3-D structure of protein, might lead to aHUS.